Validity and Reliability Analysis of Knowledge of, Attitude toward and Practice of a Case-mix Questionnaire among Turkish Healthcare Providers - Saad Ahmed Ali Jadoo; Seher Nur Sulku; Syed M. Aljunid; Ilker Dastan (Journal of Health Economics and Outcomes Research)
**Objectives:** This study was aimed to assess validation and reliability of knowledge of, attitude toward and practice (KAP) of a Case-mix and Diagnosis Related Group (DRG) system questionnaire.